Association of LPCAT1-rs8352 genetic variant with susceptibility and severity of pediatric bronchial asthma: a case-control study - Khalid M. Mohany; Yasser Gamal; Yaser F. Abdel Raheem (BMC Pediatrics)
Abstract Background This study aimed to investigate the possible association of LPCAT1-rs8352 genetic variant (single nucleotide change C to G) with the onset and severity of pediatric asthma. Additionally, the study examined the influence of LPCAT1-rs8352 genotypes on asthma-related biomarkers including blood eosinophils count (BEC), eosinophil cationic protein (ECP), high-sensitivity C-reactive protein (hs-CRP), and immunoglobulin E (IgE) and on lung function [forced expiratory volume in one second (FEV1) and the forced vital capacity (FVC)]. Patients and methods The study included ninety-six participant grouped into two groups: G1 (46 asthmatics) and G2 (50 healthy controls). ECP, hs-CRP, and total IgE serum levels were measured using their corresponding ELISA kits. Neonatal blood DNA was extracted using the Gene JET™ Whole Blood Genomic DNA Purification Mini Kit. Genotyping was performed by RT-PCR. Results A significantly higher proportion of individuals in G1 had the LPCAT1-rs8352 CC and GC genotypes compared to G2 (p < 0.001). Individuals with the CC genotype exhibited significantly more severe asthma, along with elevated levels of BEC, ECP, hs-CRP, and total IgE. Those with the GC genotype demonstrated a similar, though less severe, pattern, followed by individuals with the GG genotype. The FEV1 and FVC values showed the opposite trend, with individuals having the GG genotype exhibiting the highest lung function values. Conclusion The LPCAT1-rs8352 allele C is associated with pediatric asthma onset and severity. Further research on the LPCAT1 genetic variants may provide a deeper understanding of pediatric bronchial asthma mechanisms and lead to improved management strategies.